Augmentation with antidepressants in schizophrenia treatment: benefit or risk - Mao YM (Dove Medical Press, 2015)
Ye-Meng Mao, Ming-Dao Zhang Shanghai Mental Health Center, Shanghai Jiao Tong University School of Medicine, World Health Organization Collaborating Center for Research and Training in Mental Health, Shanghai, People’s Republic of China Abstract: We focused on the application of antidepressants in schizophrenia treatment in this review. Augmentation of antidepressants with antipsychotics is a common clinical practice to treat resistant symptoms in schizophrenia, including depressive symptoms, negative symptoms, comorbid obsessive–compulsive symptoms, and other psychotic manifestations. However, recent systematic review of the clinical effects of antidepressants is lacking. In this review, we have selected and summarized current literature on the use of antidepressants in patients with schizophrenia; the patterns of use and effectiveness, as well as risks and drug–drug interactions of this clinical practice are discussed in detail, with particular emphasis on the treatment of depressive symptoms in schizophrenia. Keywords: depressive symptoms, drug-drug interaction, antipsychotics